Phenotypic characterization of an older adult male with late-onset epilepsy and a novel mutation in ASXL3 shows overlap with the associated Bainbridge-Ropers syndrome - Verhoeven, Willem (Neuropsychiatr Dis Treat, 2018)
The additional sex combs like 3 gene is considered to be causative for the rare Bainbridge-Ropers syndrome (BRPS), which is characterized by severe intellectual disability, neonatal hypotonia, nearly absent development of speech and language as well as several facial dysmorphisms. Apart from disruptive autistiform behaviors, sleep disturbances and epileptic phenomena may be present. Here, a 47-year-old severely intellectually disabled male is described in whom exome sequencing disclosed a novel heterozygous frameshift mutation in the ASXL3 gene leading to a premature stopcodon in the last part of the last exon. Mutations in this very end 3′ of the gene have not been reported before in BRPS. The phenotypical presentation of the patient including partially therapy-resistant epilepsy starting in later adulthood shows overlap with BRPS, and it was therefore concluded that the phenotype is likely explained by the identified mutation in ASXL3.